THE PERSPECTIVE OF CLINICAL CLERKSHIP STUDENTS ON HEALTH PROTOCOLS DURING THE COVID-19 PANDEMIC ON DAILY EXERCISE ACTIVITIES - Santi Anugrahsari; Nining Parlina; Muhammad Ikhwan Zein; Ayatullah Muhammad Resza; Suryadi; Hafid Abbas (Gladi : Jurnal Ilmu Keolahragaan, 2021)
Physical exercise is essential to maintain human health. However, everybody has to apply the health protocols to prevent COVID-19 transmission during the pandemic. There is no exception; it is also applied for Clinical Clerkship Students who undergo the learning process at the Teaching Hospital. Unfortunately, no research provides a perspective on health protocol during the COVID-19 pandemic on daily exercise activities. This study aims to research the sports activities of Clinical Clerkship Students, measure knowledge about distance when exercising according to the protocol from the Ministry of Health, and describe their opinion regarding health protocols. This research conducted a mixed-method experiment that studies twenty-eight Clinical Clerkship Students. The type of sport and its frequency were evaluated using the International Physical Activity Questionnaire (IPAQ) short form. The enhancement of participants’ knowledge after watching the video and sport activity were studied descriptive quantitatively. Meanwhile, their opinion on the health protocol was analyzed qualitatively. The participants' Physical Activity Categories were 25% low, 50% moderate, and 25% high. The results showed that low and high IPAQ Catagories have a higher video post-test score, but there was no correlation. More than 75% of the students understand the contents of health protocols during exercise. We conclude that half of Clinical Clerkship Students have a moderate physical activity category and know about distance when exercising through educational videos and believe that maintaining health during a pandemic by exercising is necessary as long as they adhere to health protocols.